Cerium promoted ni/mgo catalyst for glycerol reforming - Tan, Wei Jian (2014)
Hydrogen (H2) has been considered as energy of future to substitute fossil fuel utilization. It is currently produced from hydrocarbon reforming (i.e. natural gas and petroleum) and electrolysis processes. Therefore, in the current work, magnesium oxide (MgO)-supported Ni catalyst with Cerium, Ce as a promoter was prepared to produce the synthesis gas H2 from the glycerol reforming reaction and the activity of catalyst is studied. Besides, the physicochemical properties of fresh catalysts were characterized with various techniques. BET characterization of both fresh 3 wt% and 5 wt% Ce-Ni/MgO catalysts showed that the 5 wt% Ce-Ni/MgO catalyst has larger BET specific surface area and pore diameter than the 3 wt% Ce-Ni/MgO catalyst. XRD diffraction pattern of fresh 5 wt% Ce-Ni/MgO catalyst showed peaks representing MgO at 2θ = 37.00 and NiO at 42.99, 62.41, 74.84 and 78.79. From the FESEM imaging of 5 wt% Ce-Ni/MgO catalyst, it can be observed that it is a crystalline catalyst. TGA results summarized that the magnitude of the highest peak increases as the heating ramp increases from 10 to 20 C/min. Besides that, reaction studies have found that the 3 wt% catalysts gave almost equal rate of formation of product yield (H2 and CO). From the results obtained, the glycerol conversion, XG was directly proportional with the reactant (glycerol to N2) flow ratios. Furthermore, the activation energy obtained for H2 formation rate from the current study was 27.82 kJ/mol. The fairly low Ea indicated that the catalyst was very active in promoting the hydrogen production from the glycerol